A Century of Archaeological Heritage Protection and Exhibition in China. (3rd April 2021) - Huijun, Zhao; Doyon, Luc
ABSTRACT: Over a century ago, in order to curb the looting and trafficking of archaeological relics and alongside the development of modern archaeological excavation protocols in the region, China introduced a legal framework to protect its archaeological heritage. Over the years, the concept of heritage protection and exhibition has undergone three major developments closely intertwined with the country's political and social contexts. The present review summarises the processes at the root of this specific trajectory. Following the introduction of a clear statement of ownership by the Chinese government in the 1920s, Historical Museums became the safe keepers of archaeological relics, therefore removing this heritage type from the private sphere and putting it in the public realm. Deliberations on how to preserve the authenticity and integrity of archaeological heritage in 1950s encouraged the establishment of Archaeological Site Museums, an institution where both archaeological relics and sites can be protected and put on display. Since the 21 st century, fast urbanisation and an ever-growing market for tourism accelerated the construction and increased the popularity of Archaeological Site Parks, an urban setting combining both archaeological attractions and leisure activities. In this context, archaeological heritage has become a tool fit for touristic development and economic growth.